Application of batch electrocoagulation treatment system with aluminium electrodes for simultaneous removal of organic and heavy metal contaminants from Borneo urban rivers - Nazeri, Abdul Rahman; Calvin, Jose Jol; Allene, Albania Linus; Siti Noor Linda, Taib; Arif, Parabi; Wan Wafi Shahanney, Wan Borhan; Chieng, Kwong Ming; Astisza Syahla Ludmilla, Parabi; Ester, Jose Jol; Arzona Bija, James; Airul Azhar, Jitai; Dayang Fadhilatul Aisyah, Abang Abdul Hamid (Elsevier Inc., 2024)
The challenges of sludge management and complex water treatment systems hinder the effectiveness of chemical coagulation in treating heavily contaminated urban river water. Realizing these issues, this study aims to de velop a batch electrocoagulation system using aluminum electrodes to generate in-situ aluminum hydroxide coagulants for simultaneous removal of organic contaminants and heavy metals from Borneo urban river water. Subsequent, the treatment system achieves a reduction of 91.67 % of turbidity, 98.29 % of color, 95.16 % of total suspended solids (TSS), 97.78 % of iron, 94.21 % of lead, 21.94 % of pH, and 98.58 % of chemical oxygen demand (COD) with an electric current of 5 A and a residence time of 25 min. Besides, the treated water meets the Malaysia National Water Quality Standards for Class I which making it suitable for domestic consumption. The energy consumption cost for the treatment is only RM 1.48 (USD 0.31) per cubic meter of treated water. Additionally, the analysis of the electrocoagulation flocs reveals the presence of carbon, iron, lead, and various dissolved minerals which indicates effective contaminant removal from urban river. Overall, this study monstrates the potential of the batch electrocoagulation treatment system as an effective and cost-efficient solution for treating urban river water in Borneo industrial areas.